2010
DOI: 10.1007/s10493-009-9331-6
|View full text |Cite
|
Sign up to set email alerts
|

Hosts, distribution and genetic divergence (16S rDNA) of Amblyomma dubitatum (Acari: Ixodidae)

Abstract: We supply information about hosts and distribution of Amblyomma dubitatum. In addition, we carry out an analysis of genetic divergence among specimens of A. dubitatum from different localities and with respect to other Neotropical Amblyomma species, using sequences of 16S rDNA gene. Although specimens of A. dubitatum were collected on several mammal species as cattle horse, Tapirus terrestris, Mazama gouazoubira, Tayassu pecari, Sus scrofa, Cerdocyon thous, Myocastor coypus, Allouata caraya, Glossophaga sorici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
1
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 49 publications
5
49
1
6
Order By: Relevance
“…Variations in DNA sequences encoding 16S rRNA among individuals of the same species are also common (NAVA et al, 2010), which explains the polymorphism of this marker found in the present study in comparison to the corresponding A. rotundatum sequence available in GenBank under accession number EU805569. The analysis of this marker confirmed the identification of A. rotundatum and A. dissimile and detected new sequences in these organisms that are not found in the public database, which greatly improved our confidence in the identity of the individuals, based on morphological criteria.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Variations in DNA sequences encoding 16S rRNA among individuals of the same species are also common (NAVA et al, 2010), which explains the polymorphism of this marker found in the present study in comparison to the corresponding A. rotundatum sequence available in GenBank under accession number EU805569. The analysis of this marker confirmed the identification of A. rotundatum and A. dissimile and detected new sequences in these organisms that are not found in the public database, which greatly improved our confidence in the identity of the individuals, based on morphological criteria.…”
Section: Discussionmentioning
confidence: 51%
“…The DNA sequences of this marker among species of Amblyomma are reported to have 6.4 to 20.4% identity rates. Labruna et al (2009) and Nava et al (2010) studied 24 sequences of 16S rRNA from Amblyomma and found identity ranging from 10 to 18%. The data presented herein broaden the variation range of this marker in Amblyomma species, as 28 sequences were analyzed (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…(Nava et al 2010b). Here, we report this tick on Lutreolina crassicaudata (Desmarest) for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…L. crassicaudata is a nocturnal and semi-aquatic marsupial that uses burrows close to water courses for shelter (Santori et al 2005). Thus, its ecological niche is similar to that of capybaras (H. hydrochaeris), the main host of A. dubitatum (Nava et al 2010b). We report nymphs of A. ovale on the rodents Thrichomys apereoides (Lund) and Trinomys setosus (Desmarest) for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Although this species have been getting attention in Parasitology recently (CATENACCI, GRISE, DA SILVA et al, 2010;LUX HOPPE, ARAÚJO DE LIMA, TEBALDI et al, 2010;NAVA, VENZAL, LABRUNA, et al 2010;SOUZA, ALMEIDA ADO, FREITAS et al 2010), we could find information in other fields of study such as anatomy (BARISSON, LOURO, DIAS et al, 2012). Classic titles, describe the anatomy of arterial system of the domestic animals in details (EVANS and CHRISTENSEN, 1979;GETTY, 1986;KÖNIG and LIEBICH, 2011) but not in wild carnivores.…”
Section: Introductionmentioning
confidence: 97%